PENGARUH PEMANFAATAN LIMBAH TAMBANG BAUKSIT DAERAH SANGGAU SEBAGAI PENGGANTI AGREGRAT HALUS TERHADAP KUAT TEKAN BETON - Maliq Abdul Aziz; Abdul Aziz Al Gani; Ignatius Sudarsono (DEARSIP : Journal of Architecture and Civil, 2025)
Concrete is an important component in the construction sector. Coarse and fine aggregates, water and cement are the materials needed to make concrete. To meet the need for fine aggregate in the Sanggau area, West Kalimantan, a substitute for sand is needed, namely bauxite mine waste (tailing bauxite). So it is important to consider whether tailing bauxite can be used and processed into construction materials. The aim of this research is to determine the optimum compressive strength of concrete produced by using tailing bauxite as fine aggregate in the concrete mixture within 7, 14 and 28 days. This research is a test carried out at the Concrete Laboratory, Center for Materials and Engineering Goods to collect the necessary data. By using quantitative calculation techniques, research results can be calculated to draw conclusions. From the results obtained, after 28 days of age, concrete using tailing bauxite as fine aggregate has a higher compressive strength, namely 32.20 Mpa, compared to normal concrete, namely 26.89 Mpa. Material testing, tailing bauxite have physical properties that meet specifications that can be used as a substitute for fine aggregate. The conclusion of this research is that the results of compressive strength testing show that the use of tailing bauxite as fine aggregate produces higher compressive strength values ​​compared to normal concrete. Apart from that, the use of tailing bauxite in concrete mixtures can produce more economical concrete and can reduce waste from existing bauxite mines.